Nonoperative treatment efficacy prognosis in acute small bowell obstruction - S. G. Shapovalyants; S. Ye. Larichev; Z. A. Zhemukhova; N. A. Soldatova; I. A. Smirnov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Objective is to optimize treatment strategy for patients presenting with acute small bowell obstruction (SBO) due to adhesions. We developed a prognostic scale for conservative treatment outcome utilizing multiple prognostic factors.Methods. In retrospective study case records of 385 patients for 2003–2008 have been analyzed. Patients with suspicion to strangulation were not included in investigation. According to the designed integrated prognostic system with application of Bayesian statistical methods patients have been distributed into three prognostic groups. Patients with low chances for conservative resolution of obstruction underwent surgery, i.e. adhesiolysis. Standard conservative therapy was carried out to patients with high chances. Conservative treatment that included endoscopic nasointestinal decompression (ENID) was prescribed to patients from the group of peer probability of obstruction resolution. Results. Prognostic system has been tested in 2009. During observation time 56 patients with SBO were admitted to the clinic, of them 13 were operated urgently and 43 were included into prospective study. Favourable results of standard conservative treatment were received in 68,7% of the cases (11 of 16 patients), ENID was effective in all 15 patients of this group and 22 patients with low likelihood of conservative resolution have been operated. The over-all mortality was 2,2% (1 patient of 43).Conclusion. The designed prognostic scale allows to prove with high accuracy the choice of SBO treatment method and to predict treatment outcome at this disease with high performance.